The synthesis and properties of some higher membered fused alicyclic ring systems - Horn, Denis Herbert Suttle; Horn, Denis Herbert Suttle (Department of Chemistry, 2017)
Because of the theoretical interest in the ring system consisting of two-fused fully unsaturated seven-membered rings (Wilson Baker, Tilden lecture J. 1945, 268), for which the trivial name "heptalene" is suggested, attempts have been made to synthesise this hydrocarbon to study its chemical and physical properties. The application of the Demjanov ring expansion reaction to the synthesis of seven-membered ring systems has been explored and it has been found that 2-aminomethyl-1,2,3,4-tetrahydronaphthalene undergoes the normal reaction with nitrous acid to yield derivatives of benz-cyclo-heptane. However, further attempts to apply this reaction to the synthesis of bicyclo-[0.5.5]-dodecane derivatives was abandoned because of the difficulty of preparing the required amino intermediates. The use of an intramolecular Grignard condensation for the synthesis of alicyclic ring systems has also been investigated. This approach was not followed up as difficulty was experienced in the formation of the aryl Grignard intermediates. The Buchner ring expansion of benzenoid rings to derivatives of ethyl cyclo-heptatriene carboxylate by means of ethyl diazoacetic ester has been found convenient for the synthesis of partially unsaturated [0.5.5]-bicyclo-dodecane derivatives. Thus ethyl [0.5.5]-bicyclo-dodecatriene carboxylate has been prepared by the action of ethyl diazoacetic ester on benz-cyclo-heptane. It has also been found possible to extend this reaction to the synthesis of the more unsaturated [0. 5.5]-bicyclo-dodecatetraene carboxylic acid by treating 3-acetoxy-1:2-benz-cyclo-heptane with ethyl diazoacetic ester and hydrolysing and dehydrating the hydroxy-acid so formed. However, attempts to dehydrogenate these [0.5.5]-bicyclo-dodecane systems to heptalene derivatives could not be accomplished. Instead rearrangement products such as dimethyl naphthalene and ethyl azulene were produced, clearly indicating that the heptalene structure cannot be produced with the same facility as azulenes. Attempts to reach the heptalene structure by dibromination of methyl [0.5.5J-bicyclo-dodecatetraene carboxylate and the mild dehydrobromination with diethyl aniline failed to yield the required product, once again demonstrating that the heptalene system has not the stability which is expected for a fully conjugated planar structure.